Rainfall Intensity - Dengue Fever Incidents Relationship During Rainy Season in Bantul Regency, Yogyakarta, Indonesia - Muhammad Ganang Garnida; Tri Wulandari Kesetyaningsih (CV. Inara, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus (DENV) infection. Dengue fever is spread through the bite of the female Aedes aegypti mosquito. Rainfall intensity plays a role in creating a suitable environment for vectors, thus potentially increasing the number of DHF cases. Rainfall intensity is not the same throughout the rainy season. This study aims to determine the relationship between rainfall intensity and DHF incidence at the beginning, middle, and end of the rainy season in Bantul Regency. This study is an observational analytical study with a cross-sectional design. Monthly rainfall and DHF incidence data per sub-district from 2019-2023 were obtained from the Climate Agency of Yogyakarta Province and the Bantul Regency Health Office, respectively. The results of the Spearman rank test showed a positive correlation between rainfall and DHF incidence in the middle (p = 0.005) and end (p = 0.000) of the rainy season, but no correlation at the beginning of the rainy season (p = 0.181). Thus, the control of dengue fever must be increased from the beginning of the rainy season, considering the tendency of a lag effect and the significance of rainfall with dengue fever at the peak and end of the rainy season.